The Effect of the Round Club Learning Model on the Collaboration Skills in IPAS of Fourth-Grade Elementary School Students - nursari nursari; rosmolah rosmalah; awaluddin muin (PT. Lontara Digitech Indonesia, 2026)
This research is a pre-experimental study that aims to determine the effect of the Round Club learning model on improving the IPAS collaboration skills of fourth-grade students at SD Inpres 10/73 Bajoe, Bone Regency. The research design used was the One-Group Pretest-Posttest Design. The population in this study consisted of all fourth-grade students of SD Inpres 10/73 Bajoe, Bone Regency, with a sample of 25 students selected using saturated sampling technique. The data collection technique used was a questionnaire, namely pretest and posttest questionnaires, to measure students’ collaboration skills before and after the implementation of the Round Club learning model. The data analysis techniques used were descriptive statistics and inferential statistics. The results of the descriptive statistical analysis showed that the average pretest score of students’ collaboration skills was in the fair category with a score of 65.84 and increased in the posttest average score to 73.52, which was in the good category. This increase indicates a change in students’ collaboration skills after the implementation of the Round Club learning model in IPAS learning. Based on the results of inferential statistical analysis using the paired samples t-test, the tcount value was 8.418, which was greater than the ttable value of 2.06390 (8.418 > 2.06390), meaning that there was a significant difference in students’ collaboration skills before and after the implementation of the Round Club learning model. Since the posttest average score was higher than the pretest average score and the test results showed a significant difference, it can be concluded that the Round Club learning model has an effect on improving the IPAS collaboration skills of fourth-grade students at SD Inpres 10/73 Bajoe, Bone Regency